Design and development of an automated inspection system for train suspension spring coil - Zhan Qing, Lim (2018)
This project describes the process to design and development an automated train suspension spring coil inspection system. The project is in collaboration with SMRT Trains Ltd to improve train reliability by providing greater accuracy of the result when inspecting the spring coil by eliminating human error in the inspection. The current method used by the inspector to inspect the spring coil is by manually moving the Non-Destructive Testing (NDT) probe along the surfaces of the spring coil. This method is proven to be very tedious and inaccurate as certain surface area might be missed out by the inspector due to its complex geometry. In addition, the spring coil is heavy, it is difficult for the inspector to rotate the spring coil during the scan. The design solution is automated the whole inspection process by the use of motorised mechanism and a programmable controller to inspect the geometry of the suspension spring coil without the needs of human intervention. The prototype design uses a motor to rotate the spring coil while the inspection probe will be attached to several moving arms that will be programmed to move linearly into spring to scan the surface area. In order to achieved precise linear movement of the probing arms, stepper motors and timing belt drive system was used in this project. This configuration is similar to computer numeric control (CNC) machines where precise motion is required. The final prototype was tested and proven to be working according to the design specification. However, the system was not tested using actual NDT inspection instruments as the supplier did not provide the instruments at the time of the project. Hence, future work of the project may include integration of the NDT instruments into this inspection system and evaluating the effectiveness of the system.